Development of Animal Thematic "Si Buyung" Gymnastics - Desy Arisandy; Bangkit Seandi Taroreh (JUARA : Jurnal Olahraga, 2023)
The aims of this study were 1) produce physical-motor activity media products in the form of animal thematic "si buyung" gymnastics, 2) find out the implementation of physical-motor activity media in the form of animal thematic "si buyung" gymnastics in learning. The research method uses the ADDIE research development (R and D) approach. The research population of early childhood education students in Palembang City. The sample is 30 students with a purposive sample. The criteria are as follows 1) is a tri dharma partner school of higher education with Bina Darma University, 2) 4-6 years old. The research instrument uses a questionnaire. Data analysis techniques using quantitative analysis. The results of the study were: 1) physical-motor activity media products in the form of animal thematic â€œsi buyungâ€ gymnastics, 2) physical-motor activity media products show "appropriate use" with a percentage of 71%, but in practice they still need parental and teacher guidance and assistance